Finite deformations of two drops due to electric field (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 2002)
The finite deformations of two drops due to electric field are investigated in this article. The radii of the drops and the fluid phases could be different. Reynolds' number is assumed small enough to solve the problem in quasisteady Stokes' approximation. It is also supposed that the initial form of the drops is spherical and the fluids are homogeneous, incompressible and Newtonian.The electric and hydrodynamic problems are separated and the electric one has an influence on the hydrodynamic one through the boundary conditions. The Maxwell's equations are turned to Laplace's equations, and together with Stokes' equations they are solved by semianalytical-seminumerical method. We use boundary-integral type of these equations to solve them by the method of boundary elements. The kinematic condition gives a new form to the particles.The result obtained indicate that interactions between two and three fluid phases, due to electric field, lead to deformations of the drops. The influence over the deformations of some dimensionless parameters of the problem has been given graphically.